African Peace and Security Architecture (APSA) subsidiarity and the Horn of Africa: the Intergovernmental Authority on Development (IGAD) - Sousa, Ricardo Real P. de (2013)
The new African Peace and Security Architecture is based on the principle of subsidiarity governing the relationship between the United Nations, African Union and regional mechanisms. Nevertheless it is still unclear how subsidiarity will be implemented in the decision-making mechanism, division of labour and burden sharing. This paper analyses the challenges of subsidiarity in two IGAD processes: the renewal of the security mandate started at IGAD in 2005 and Ethiopian intervention in Somalia in 2006. It finds that regional rivalries and historical legacies prevent the development of IGAD’s security mandate and an intervention policy while international interests determine the projection of the Somalia case. It concludes that sub-regional inter-state institutional coordination and capacity-building are essential requirements for the implementation of subsidiarity.